Impact of diabetes remission or progression on the incidence of cardiovascular disease in Japan: historical cohort study using a nationwide claims database - Chihiro Shimayama; Kazuya Fujihara; Laymon Khin; Hiroki Takizawa; Chika Horikawa; Takaaki Sato; Masaru Kitazawa; Yasuhiro Matsubayashi; Takaho Yamada; Hirohito Sone (Cardiovascular Diabetology)
Abstract Background Previous studies demonstrated that diabetes remission can occur during intensive intervention and in real-world settings. However, the impact of diabetes remission in real-world settings on the incidence of cardiovascular disease (CVD) remains unclear. Methods This retrospective cohort study included 299,967 individuals aged 20–72 years who underwent multiple checkups between 2008 and 2020 and completed ≥ 3 years of follow-up. Patients were divided into four groups according to changes in glycated hemoglobin levels and the use of diabetes medications during the 1-year baseline period: diabetes mellitus (DM)+/no remission, DM+/remission, DM−/no progression, and DM−/progression. The risk of CVD was evaluated using multivariable Cox regression analysis. Results The median follow-up period was 5.0 years. The rates of CVD in the DM+/no remission, DM+/remission, DM−/no progression, and DM−/progression groups were 7.96, 4.76, 1.99, and 5.47 per 1000 person-years, respectively. Compared with DM+/no remission, DM+/remission reduced the risk of CVD [hazard ratio (HR) = 0.71, 95% confidence interval (CI) = 0.57–0.89]. Meanwhile, the HR for CVD in the DM+/remission group was 0.75 (95% CI = 0.56–0.99) for change in BMI ≤ 0%, versus 0.66 (95% CI = 0.45–0.96) for change in BMI > 0%. Conclusions In a real-world setting without intensive intervention, diabetes remission decreased the risk of CVD by approximately 30% regardless of changes in BMI, suggesting that diabetes remission can prevent CVD without weight loss in routine care and emphasizing the importance of achieving remission. Graphical Abstract